Fluctuation characteristics of the TCV snowflake divertor measured with high speed visible imaging. (28th September 2018) - Walkden, N R; Labit, B; Reimerdes, H; Harrison, J; Farley, T; Innocente, P; Militello, F
Abstract: Tangentially viewing fast camera footage of the low-field side snowflake minus divertor in TCV is analysed across a four-point scan in which the proximity of the two X-points is varied systematically. The motion of structures observed in the post-processed movie shows two distinct regions of the camera frame exhibiting differing patterns. One type of motion in the outer scrape-off layer remains present throughout the scan whilst the other, apparent in the inner scrape-off layer between the two nulls, becomes increasingly significant as the X-points contract towards one another. The spatial structure of the fluctuations in both regions is shown to conform to the equilibrium magnetic field. When the X-point gap is wide the fluctuations measured in the region between the X-points show a similar structure to the fluctuations observed above the null region, remaining coherent for multiple toroidal turns of the magnetic field and indicating a physical connectivity of the fluctuations between the upstream and downstream regions. When the X-point gap is small the fluctuations in the inner scrape-off layer between the nulls are decorrelated from fluctuations upstream, indicating local production of filamentary structures. The motion of filaments in the inter-null region differs, with filaments showing a dominantly poloidal motion along magnetic flux surfaces when the X-point gap is large, compared to a dominantly radial motion across flux-surfaces when the gap is small. This demonstrates an enhancement to cross-field transport between the nulls of the TCV low-field-side snowflake minus when the gap between the nulls is small.